Preparation method of large-thickness, large-density and high-purity vertical carbon nanotube array thermal interface material
By optimizing the ratio between the transition layer and the catalyst layer and multi-stage hydrogen inlet technology, the problem of difficulty in preparing large-thick and large-density vertical carbon nanotube arrays in the prior art is solved, and high-performance thermal interface material preparation is achieved.
Patent Information
- Application Number
- CN202510318854.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-06-24
AI Technical Summary
The prior art is difficult to prepare a high-thickness, high-density, and high-purity vertical carbon nanotube array, which limits its application in high-performance devices.
By optimizing the ratio of the transition layer to the catalyst layer and using multi-stage hydrogen-assisted growth, vertical carbon nanotube arrays are prepared using catalytic chemical vapor deposition technology.
The preparation of high-thickness, large-density, and high-purity vertical carbon nanotube arrays has been achieved, which improves its thermal conductivity and performance, and meets the needs of thermal interface materials under high power density.
Smart Images

Figure CN120193245A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of vertical carbon nanotube array thermal interface materials, and particularly to a preparation method of a vertical carbon nanotube array thermal interface material with large thickness, large density, and high purity. Background Art
[0002] Vertical carbon nanotube arrays were first synthesized in 1996. Due to their unique structure, they have excellent mechanical, electrical, and thermal properties and are widely used in fields such as electronic devices, composite materials, energy storage, thermal management, biomedicine, etc., and are also used as field emission displays, thermally and electrically conductive composite materials, fuel cells, thermal interface materials, heat dissipation devices, biological scaffolds, and drug carriers. However, the catalyst thickness used in existing preparation methods is often low, and the ratio with the transition layer is unreasonable, so it is difficult to obtain vertical carbon nanotube arrays with large thickness and large density, which limits their application in high-performance devices.
[0003] During the preparation of vertical carbon nanotube arrays, the catalyst needs to have high activity to promote the decomposition of carbon source gas and the growth of carbon nanotubes, and at the same time, it needs to remain stable at high temperatures to avoid sintering or deactivation. However, catalysts with high activity often have poor stability and are difficult to maintain activity during a long growth process. Currently, the catalysts commonly used to synthesize vertical carbon nanotube arrays are magnetic materials such as Fe, Co, Ni, etc. Literature 1 (Ceram. Int., 2024; 50(11): 20749 - 20757) uses AZO as the transition layer material, Fe as the catalyst, nitrogen, ethylene, and hydrogen as the atmosphere to grow at 650 °C for 30 min, and prepares vertical carbon nanotube arrays with a height of only 8 - 13 μm and contains more amorphous carbon. Chinese Patent CN202010441415.8 discloses a catalytic chemical vapor deposition (CCVD) method with Al2O3 as the transition layer, but does not optimize the thickness ratio of the transition layer and the catalyst layer, and prepares vertical carbon nanotube arrays with a thickness of only dozens of μm and weak orientation.
[0004] The characteristics of the above methods are that metal oxide materials are used as the transition layer to protect the catalyst from poisoning, so that during the growth process, the catalyst can effectively etch the substrate, and fully exert its ability to dissolve and precipitate carbon, form a solid solution with free carbon atoms, and based on the vapor - liquid - solid (VLS) growth mechanism, form nucleation sites on the substrate to promote the directional growth of carbon nanotubes. However, the above methods have not deeply optimized the ratio of the transition layer and the catalyst layer, and have not regulated the orientation and crystallinity of the vertical carbon nanotube arrays, so that their thermal conduction and electrical transport capabilities have not reached the expected level. Summary of the Invention
[0005] The key technical problem to be solved by the present invention is: optimizing the ratio of the transition layer to the catalyst layer, and simultaneously introducing hydrogen in multiple segments to assist in the growth of the vertical carbon nanotube array. Based on the catalytic chemical vapor deposition technology, a vertically aligned carbon nanotube array with large thickness, high density, and high thermal conductivity can be controllably prepared to meet the urgent requirements of thermal interface materials under high power density.
[0006] The technical solution of the present invention is as follows:
[0007] The present invention provides a method for preparing a thermal interface material of a vertically aligned carbon nanotube array with large thickness, high density, and high purity, comprising the following steps:
[0008] (1) Using C2H4 as a carbon precursor, He as an inert protective gas, Ar / H2 as a reducing gas, Al2O3 as a transition layer, and Fe as a catalyst layer for batching;
[0009] Preferably, in step (1), the volume ratio of Ar to H2 in the reducing gas Ar / H2 is 95:5, and the volume ratio of C2H4, He, and the reducing gas is 1:(4 - 8):(4 - 8). The volume flow ratio of the above gases is 50 sccm:(200 - 400 sccm):(200 - 400 sccm).
[0010] Preferably, in step (1), the thickness ratio of Al2O3 to Fe is (3.5 - 5.5):1. The thickness ratio is obtained by testing with a film thickness gauge. During EBE coating, high-energy ions bombard the target to melt it and deposit it on the substrate, which has nothing to do with the density of the target. If the thickness ratio is too small, that is, the amount of Fe catalyst added is too much, the catalyst will form clusters during the etching process, reducing the catalytic ability; if the thickness ratio is too large, too much Al2O3 will cause the catalyst to be too dispersed, and the growth density of the array will decrease.
[0011] (2) Using electron beam evaporation, depositing Al2O3 and Fe on a Si substrate to obtain a substrate material;
[0012] Preferably, in step (2), the thickness ratio of Al2O3 to Fe is (21 - 33 nm):6 nm, and the size of the Si substrate is 10×10×1 mm.
[0013] Preferably, in step (2), the specific parameters of the electron beam evaporation are a beam current of 45 A and an evaporation rate of 0.16 A / s.
[0014] (3) Cleaning and then drying the substrate material prepared in step (2);
[0015] Preferably, in step (3), the base material is rinsed in acetone, ethanol and deionized water for 5 min each, and then placed in a drying oven for drying at a temperature of 60° C. for 30 min.
[0016] (4) placing the substrate cleaned in step (3) in a quartz boat of a tubular furnace, raising the furnace temperature to 550-600°C under the protection of He gas, while introducing Ar / H2 in a stepwise manner, and continuing to raise the temperature to 750-800°C, introducing C2H4 to grow a vertical carbon nanotube array, thereby obtaining the thickest, densest and most pure vertical carbon nanotube array.
[0017] Preferably, in step (4), the size of the quartz boat is 50×12×5 mm, and the heating rate is 5-10° C. / min.
[0018] Preferably, in step (4), the initial flow rate of Ar / H2 introduced in a stepwise manner is 200 sccm, and the reducing gas Ar / H2 is introduced at a rate of 50 sccm for every 50°C increase in temperature, that is, when the growth stage (750-800°C) is reached, 400 sccm of reducing gas Ar / H2 is introduced, wherein the volume ratio of Ar to H2 in Ar / H2 is 95:5. The initial flow rate of Ar / H2 is of great significance to the growth of carbon nanotube arrays. If the initial flow rate is too large, the decomposition rate of the carbon source may be accelerated, resulting in the rapid deposition of disordered carbon; if the initial flow rate is too small, the concentration of active metal particles formed by the catalyst will be reduced. As the growth proceeds, the carbon source concentration in the tube will slowly increase. If the amount of reducing gas added is too large / too small, the excess hydrogen concentration in the growth process will increase, which will destroy the dynamic balance between carbon deposition and etching, increase the amorphous carbon content, and reduce the quality of the array.
[0019] Preferably, in step (4), the deposition pressure is 0.03 MPa, and after the temperature is raised to 750-800°C, the flow rate of C2H4 introduced is 40sccm, and the temperature is kept for 50-60 minutes to grow the vertical carbon nanotube array; finally, He gas is introduced to slowly cool it to below 200°C, and the tubular furnace is turned on to obtain the thickest, densest and most pure vertical carbon nanotube array.
[0020] The present invention also provides a vertical carbon nanotube array prepared by the method, which has a thickness of 120-200 μm and a density of 10 10 -10 11 Root / cm 2 , thermal conductivity is 112-155W / m·K.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] (1) The present invention formulates the ingredients according to the thickness ratio of Al2O3:Fe = (21 - 33 nm):6 nm to synthesize a higher-quality vertical carbon nanotube array. Compared with the traditional formulation (Al2O3:Fe = 16.7 nm:2.8 nm), the content of Fe is increased, which directly improves the growth density and height of the carbon nanotubes. Specifically, the increase in the iron content can improve the catalyst particle density and the carbon source cracking efficiency, significantly enhancing the growth density and height of the carbon nanotubes. However, if too much iron is added, the catalytic efficiency will decrease due to particle agglomeration, limited carbon diffusion, and side reactions. The optimal iron content needs to be determined experimentally by balancing the nucleation density, particle size, and carbon supply rate. Usually, there is a critical threshold, and the threshold in the present invention is 6 nm.
[0023] (2) The process flow of the present invention is simple and the parameters are stable. Under a slightly positive deposition pressure (0.03 MPa), a high-quality vertical carbon nanotube array can be obtained.
[0024] (3) In the initial stage of growth, the catalyst Fe etches the substrate to form initial nucleation sites with carbon atoms. Therefore, the etching rate and uniformity of the catalyst are closely related to the growth rate of the carbon nanotubes. The present invention uses electron beam evaporation to deposit Fe uniformly on the substrate, and a relatively thick transition layer is used to prevent the catalyst from being poisoned during the etching process, directly increasing the initial nucleation sites, providing an initial orientation effect for the directional growth of the vertical carbon nanotube array, and increasing the growth rate of the carbon nanotubes.
[0025] (4) During the growth process, Ar / H2 is introduced in a multi-stage and gradient manner, avoiding the structure with a large amount of amorphous carbon at the top of the vertical carbon nanotube array obtained by the traditional process, improving the crystallinity and purity in the array, and effectively reducing the contact thermal resistance between the top of the array and the heat sink, which is beneficial to the interfacial heat transport of the vertical carbon nanotube array.
[0026] The specific process of the above multi-stage and gradient introduction of Ar / H2 is as follows: 1. Low hydrogen concentration in the initial stage: Promote nucleation and catalyst activation. A lower hydrogen concentration in the initial stage gently reduces the catalyst precursor to form nanoscale active metal particles, avoiding catalyst particle agglomeration or inactivation caused by over-reduction. Too high a hydrogen concentration may accelerate the carbon source decomposition rate, leading to the rapid deposition of disordered carbon. The low hydrogen condition in the initial stage can slow down the carbon deposition rate and promote the orderly arrangement of carbon atoms into a graphitized structure. 2. Gradually increase hydrogen in the middle stage: Dynamically balance carbon deposition and etching. As the hydrogen concentration gradually increases, hydrogen reacts with amorphous carbon (sp 3 hybridized carbon) (such as generating volatile products such as CH4 or C2H2), selectively removing the disordered carbon structure, while the structurally complete carbon nanotubes (sp 2The hybrid is retained due to its chemical inertness; hydrogen can maintain the metallic state of the catalyst particles and prevent them from being deactivated by carbon coverage. The gradient hydrogen addition avoids excessive etching or coarsening of the catalyst particles by a high hydrogen concentration at one time, ensuring the continuous catalysis of carbon nanotube growth. 3. High hydrogen concentration in the later stage: stabilizing the vertical orientation and suppressing side reactions. The high-concentration hydrogen inhibits the formation of non-catalytic pyrolytic carbon (directly decomposed from the gaseous carbon source), and at the same time scavenges residual carbon and hydrogen free radicals, reducing the contamination of the array by by-products. In the later stage of growth, the high hydrogen concentration may repair the defects (such as pentagonal rings and heptagonal rings) on the carbon nanotube wall through local etching, improving its crystallinity.
[0027] (5) The formula used in the present invention can prepare a large-thickness and high-purity vertical carbon nanotube array thin film material because it avoids the low-height vertical carbon nanotube array and amorphous carbon structure caused by low-concentration catalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following will briefly introduce the drawings required for the description of the embodiments. Obviously, the following drawings are only some embodiments of the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative efforts.
[0029] Figure 1 It is a SEM picture of a large-thickness, large-density, and high-purity vertical carbon nanotube array prepared in Embodiment 1 of the present invention.
[0030] Figure 2 It is a SEM picture of a large-thickness, large-density, and high-purity vertical carbon nanotube array prepared in Embodiment 2 of the present invention.
[0031] Figure 3 It is a SEM picture of a sparse and low vertical carbon nanotube array prepared in Comparative Example 1 of the present invention.
[0032] Figure 4 It is a SEM picture of a low-purity vertical carbon nanotube array prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0033] To make the technical problems, technical solutions, and advantages to be solved by the present invention clearer, the following will be described in detail with reference to the drawings and specific embodiments.
[0034] Embodiment 1
[0035] 1) According to the thickness of Al2O3:Fe (21nm:6nm), the transition layer Al2O3 and Fe are deposited on the Si substrate in sequence by electron beam evaporation (beam current 45A, evaporation rate 0.16A / s). 2) The substrate is rinsed in acetone, ethanol, and deionized water for 5 minutes in sequence, and dried in a drying oven at 60℃ for 30 minutes. 3) The deposition pressure is 0.03MPa, and under the protection of He gas, it is increased to 550℃ at a rate of 10℃ / min, and Ar / H2 is introduced in a step-by-step manner (in Ar / H2, the volume ratio of Ar to H2 is 95:5, the initial flow rate is 200sccm, and an additional 50sccm is added for each 50℃ increase in temperature); until 40sccm of C2H4 is introduced at 750℃, and the temperature is kept for 50min, a vertical carbon nanotube array with large thickness, high density and high purity is obtained. The thermal conductivity test result using the harmonic method is 112W / m·K. The SEM spectrum of the material is shown in Figure 1 The carbon nanotube array has a height of 120 μm and a density of 0.20 g / cm 3 .
[0036] Embodiment 2
[0037] 1) According to the thickness of Al2O3:Fe (33nm:6nm), the transition layer Al2O3 and Fe are deposited on the Si substrate in sequence by electron beam evaporation (beam current 45A, evaporation rate 0.16A / s). 2) The substrate is rinsed in acetone, ethanol, and deionized water for 5 minutes in sequence, and dried in a drying oven at 60℃ for 30 minutes. 3) The deposition pressure is 0.03MPa, and under the protection of He gas, it is increased to 600℃ at a rate of 10℃ / min, and Ar / H2 is introduced in a step-by-step manner (in Ar / H2, the volume ratio of Ar to H2 is 95:5, the initial flow rate is 200sccm, and an additional 50sccm is added for each 50℃ increase in temperature); until 40sccm of C2H4 is introduced at 800℃, and the temperature is kept for 50min to obtain a vertical carbon nanotube array with large thickness, high density and high purity. The thermal conductivity test result using the harmonic method is 155W / m·K. The SEM spectrum results of the material are shown in Figure 2 The carbon nanotube array has a height of 200 μm and a density of 0.30 g / cm 3 . It can be seen that the array height, density and collimation are better (the bent part is scratched by tweezers during SEM testing). This is because the increase of Al2O3 can make the catalyst form more uniform active particles during the reaction process, inhibiting the cluster formation during the catalyst etching process, thereby increasing the density of nucleation sites and making the growth density of carbon nanotubes higher. The increase in effective active particles of the catalyst and the limited increase in temperature promote its ability to dissolve and precipitate carbon, which significantly increases the array height. In summary, the limited heat transfer path of the array is increased, which improves the thermal conductivity to a certain extent.
[0038] Comparative Example 1
[0039] 1) According to the thickness of Al2O3:Fe (16.7nm:2.8nm), the transition layers of Al2O3 and Fe are deposited on the Si substrate in sequence by electron beam evaporation (beam current 45A, evaporation rate 0.16A / s). 2) The substrate is rinsed in acetone, ethanol, and deionized water for 5 minutes in sequence, and dried in a drying oven at 60°C for 30 minutes. 3) The deposition pressure is 0.03MPa, and under the protection of He gas, it is increased to 550°C at a rate of 10°C / min, and Ar / H2 is introduced in a step-by-step manner (in Ar / H2, the volume ratio of Ar to H2 is 95:5, the initial flow rate is 200sccm, and an additional 50sccm is added for every 50°C increase in temperature); until 40sccm of C2H4 is introduced at 750°C, and the temperature is kept for 50 minutes to obtain a vertical carbon nanotube array in comparative example 1. The SEM spectrum of this material is shown in Figure 3 The height of the carbon nanotube array is 64 μm and the density is 0.08 g / cm 3 , the distribution is sparse and the collimation is poor. This is because the catalyst content is low, the initial nucleation sites are insufficient, resulting in a decrease in the density of the array, and the van der Waals force between the carbon tubes is weakened, causing them to grow obliquely.
[0040] Comparative Example 2
[0041] 1) According to the thickness of Al2O3:Fe (21nm:6nm), the transition layers of Al2O3 and Fe are deposited on the Si substrate in sequence by electron beam evaporation (beam current 45A, evaporation rate 0.16A / s). 2) The substrate is rinsed in acetone, ethanol, and deionized water for 5 minutes in sequence, and dried in a drying oven at 60°C for 30 minutes. 3) The deposition pressure is 0.03MPa, and under the protection of He gas, it is increased to 550°C at a rate of 10°C / min, and Ar / H2 is directly introduced (in Ar / H2, the volume ratio of Ar to H2 is 95:5, and the Ar / H2 flow rate is constant at 400sccm); at 750°C, 40sccm of C2H4 is introduced and kept warm for 50 minutes to obtain the vertical carbon nanotube array of comparative example 2. The SEM spectrum of this material is shown in Figure 4 The height of the carbon nanotubes is 115 μm and the density is 0.17 g / cm 3 , the density and collimation are better, but there are more amorphous carbon and carbon nanotube cluster structures on the top. This is because the excessively high initial reducing gas flow rate will enhance the scouring effect of the gas flow on the catalyst precursor (such as metal oxide), resulting in uneven distribution of catalyst particles on the substrate surface, and even agglomeration to form large-sized particles. Large particle catalysts will promote the formation of multi-layer carbon nanotubes or amorphous carbon, reducing the uniformity of the array.
[0042] As described above, it is only the specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art within the technical scope disclosed by the present invention can easily think of changes or substitutions, which should all be covered within the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims described.
Claims
1. A method for preparing a thick, high-density, high-purity vertical carbon nanotube array thermal interface material, characterized in that: The following steps are involved: (1) C2H4 is used as a carbon precursor, He is used as an inert protective gas, Ar / H2 is used as a reducing gas, Al2O3 is used as a transition layer, and Fe is used as a catalyst layer; (2) using electron beam evaporation to deposit Al2O3 and Fe on a Si substrate to obtain a substrate material; (3) washing and drying the base material prepared in step (2); (4) placing the substrate cleaned in step (3) in a quartz boat of a tubular furnace, raising the furnace temperature to 550-600°C under the protection of He gas, while introducing Ar / H2 in a stepwise manner, and continuing to raise the temperature to 750-800°C, introducing C2H4 to grow a vertical carbon nanotube array, thereby obtaining the thickest, densest and most pure vertical carbon nanotube array.
2. The method for preparing a thick, dense, and high-purity vertical carbon nanotube array thermal interface material according to claim 1, characterized in that: In step (1), the volume ratio of Ar to H2 in the reducing gas Ar / H2 is 95:5, and the volume flow ratio of C2H4, He and the reducing gas is 50sccm:(200-400sccm):(200-400sccm).
3. The method for preparing a thick, dense, and high-purity vertical carbon nanotube array thermal interface material according to claim 2, characterized in that: In step (1), the thickness ratio of Al2O3 to Fe is (3.5-5.5):
1.
4. The method for preparing a thick, dense, and high-purity vertical carbon nanotube array thermal interface material according to claim 1, characterized in that: In step (2), the thickness ratio of Al2O3 to Fe is (21-33nm): 6nm, and the size of the Si substrate is 10×10×1mm.
5. The method for preparing a thick, dense, and high-purity vertical carbon nanotube array thermal interface material according to claim 4, characterized in that: In step (2), the specific parameters of the electron beam evaporation are a beam current of 45A and an evaporation rate of 0.16A / s.
6. The method for preparing a thick, dense, and high-purity vertical carbon nanotube array thermal interface material according to claim 1, characterized in that: In step (3), the base material is rinsed in acetone, ethanol and deionized water for 5 minutes each, and the drying temperature is 60° C. and the drying time is 30 minutes.
7. The method for preparing a thick, dense, and high-purity vertical carbon nanotube array thermal interface material according to claim 1, characterized in that: In step (4), the size of the quartz boat is 50×12×5 mm, and the heating rate is 5-10° C. / min.
8. The method for preparing a thick, dense, and high-purity vertical carbon nanotube array thermal interface material according to claim 7, characterized in that: In step (4), the initial flow rate of Ar / H2 introduced in a stepwise manner is 200 sccm, and the reducing gas Ar / H2 is introduced at a rate of 50 sccm for every 50°C increase in temperature, wherein the volume ratio of Ar to H2 in Ar / H2 is 95:
5.
9. The method for preparing a thick, dense, and high-purity vertical carbon nanotube array thermal interface material according to claim 8, characterized in that: In step (4), the deposition pressure is 0.03MPa, and after the temperature is raised to 750-800°C, the flow rate of C2H4 is 40sccm, and the temperature is kept for 50-60min to grow the vertical carbon nanotube array; finally, He gas is introduced to slowly cool it to below 200°C, and the tubular furnace is turned on to obtain the thickest, densest and most pure vertical carbon nanotube array.
10. The vertical carbon nanotube array prepared by the method according to any one of claims 1 to 9, characterized in that: The carbon nanotube array has a thickness of 120-200 μm and a density of 10 10 -10 11 Root / cm 2 , thermal conductivity is 112-155W / m·K.
Citation Information
Patent Citations
Preparation method of vertical carbon nanotube arrays for high absorptivity materials
CN111455339B